The phytoremediation using water hyacinth and water lettuce : correlation between sugar content, biomass growth rate, and nutrients - Nur Azmira Zainuddin,; Mohd Fadhil Md Din,; Maria Nuid,; Khairunnisa Abdul Halim,; Nur Atikah Abdul Salim,; Siti Hanna Elias,; Zainab Mat Lazim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Degradation of water quality due to the presence of pollutants in water is an emerging issue in many countries, including Malaysia. Phytoremediation is one of the environmentally friendly, cost-effective conventional technologies that are still used in modern times. However, the selection of plant species is the most important aspect for the application of phytoremediation in wastewater treatment. Nevertheless, there are species of floating aquatic macrophytes that are capable of coping with various pollutants present in wastewater. Among the various floating aquatic macrophyte species, water hyacinth (WH) and water lettuce (WL) have been described as effective phytoremediators in reducing water pollution through bioaccumulation in their body tissues. Hence, WH and WL were chosen in this study as it is easily found, propagated, and cultivated. This paper aims to determine the biosorption capacity of these species in eliminating various pollutants present in wastewater as well as to define the optimum harvesting time for each species. Although these floating aquatic macrophytes are considered the most problematic plants due to their uncontrollable growth in water bodies worldwide, their ability to remove pollutants from wastewater has created a sustainable approach for their use in phytoremediation. In this sense, the use of phytoremediation by implementing the invasive floating aquatic macrophytes can certainly support the sustainable management of wastewater treatment in the future. Based on the results, it was found that WH efficiently removed higher PO4 3-, NO3 - and NO2 - concentrations compared to WL from the wastewater. Both WH and WL showed the same trend of correlation between the growth rate and sugar content, where the sugar content increased when the plants reached the highest growth rate. The maximum nutrient uptake occurred in 14-17 days, proving that nutrient availability is critical for plant growth. This study concludes that the sugar content of WH and WL are increased with the biomass growth rate, and both plants species are competent in eradicating the nutrient pollution in wastewater. On top of that, this study infers that the maximum harvesting period for WH biomass is on day 18, while WL biomass is on day 21; based on the highest sugar content and biomass weight of each species.